Passive Facebook usage undermines affective well-being: Experimental and longitudinal evidence - Verduyn, Philippe; Lee, David Seungjae; Park, Jiyoung; Shablack, Holly; Orvell, Ariana; Bayer, Joseph; Ybarra, Oscar; Jonides, John; Kross, Ethan (Journal of experimental psychology. General, 2015)
Prior research indicates that Facebook usage predicts declines in subjective well-being over time. How does this come about? We examined this issue in 2 studies using experimental and field methods. In Study 1, cueing people in the laboratory to use Facebook passively (rather than actively) led to declines in affective well-being over time. Study 2 replicated these findings in the field using experience-sampling techniques. It also demonstrated how passive Facebook usage leads to declines in affective well-being: by increasing envy. Critically, the relationship between passive Facebook usage and changes in affective well-being remained significant when controlling for active Facebook use, non-Facebook online social network usage, and direct social interactions, highlighting the specificity of this result. These findings demonstrate that passive Facebook usage undermines affective well-being.